Novel RPTPγ and RPTPζ splice variants from mixed neuron–astrocyte hippocampal cultures as well as from the hippocampi of newborn and adult mice - Taki, Sara; Boron, Walter F.; Moss, Fraser J. (Frontiers in Physiology, 2024)
Receptor protein tyrosine phosphatases γ and ζ (RPTPγ and RPTPζ) are transmembrane signaling proteins with extracellular carbonic anhydrase–like domains that play vital roles in the development and functioning of the central nervous system (CNS) and are implicated in tumor suppression, neurodegeneration, and sensing of extracellular [CO2] and [HCO3−]. RPTPγ expresses throughout the body, whereas RPTPζ preferentially expresses in the CNS. Here, we investigate differential RPTPγ-RPTPζ expression in three sources derived from a wild-type laboratory strain of C57BL/6 mice: (a) mixed neuron–astrocyte hippocampal (HC) cultures 14 days post isolation from P0–P2 pups; (b) P0–P2 pup hippocampi; and (c) 9- to 12-week-old adult hippocampi. Regarding RPTPγ, we detect the Ptprg variant-1 (V1) transcript, representing canonical exons 1–30. Moreover, we newly validate the hypothetical assembly [XM_006517956] (propose name, Ptprg-V3), which lacks exon 14. Both transcripts are in all three HC sources. Regarding RPTPζ, we confirm the expression of Ptprz1-V1, detecting it in pups and adults but not in cultures, and Ptprz1-V3 through Ptprz1-V7 in all three preparations. We newly validate hypothetical assemblies Ptprz1-X1 (in cultures and pups), Ptprz1-X2 (in all three), and Ptprz1-X5 (in pups and adults) and propose to re-designate them as Ptprz1-V0, Ptprz1-V2, and Ptprz1-V8, respectively. The diversity of RPTPγ and RPTPζ splice variants likely corresponds to distinct signaling functions, in different cellular compartments, during development vs later life. In contrast to previous studies that report divergent RPTPγ and RPTPζ protein expressions in neurons and sometimes in the glia, we observe that RPTPγ and RPTPζ co-express in the somata and processes of almost all HC neurons but not in astrocytes, in all three HC preparations.